The ENTER study (E-DetectioN Tool for Emerging Mental DisoRders): general population recruitment and data integrity in online screening for psychosis risk - Wallman, Phoebe; Estradé, Andrés; Azis, Matilda; Haining, Kate; Liang, Xinyi; Spencer, Thomas J.; Diederen, Kelly; Provenzani, Umberto; Uhlhaas, Peter J.; Fusar-Poli, Paolo (Frontiers in Psychiatry, 2025)
IntroductionEffective detection of young people at clinical high-risk for psychosis (CHR-P) is one of the rate-limiting steps in improving outcomes through preventive treatment. ENTER (E-DetectioN Tool for Emerging Mental DisoRders) was developed to refine and increase the specificity of e-detection strategies to identify young people in the community who might be exhibiting emerging symptoms of psychosis. This paper aimed to outline the ENTER procedure and data validation process and the characteristics of the self-selected sample.MethodsThe ENTER study was conducted across sites in London, Glasgow (UK), and Pavia (Italy). Participants from the general population aged 12–35 years were recruited through universities, colleges, flyers, and social media. The online screener collected data on demographics, cognition, speech, environmental risk and protective factors, and frequent subthreshold features that characterise emerging psychotic disorders.ResultsA total of 8,009 participants completed the screener over a period of 3 years. However, only 2,540 responses (32%) were deemed valid. The mean age of the participants was 23 years. The majority were women (77%), identified as white (70%), and had some experience in higher education (82%). Nearly half of the valid sample (48%) scored ≥6 on the Prodromal Questionnaire (PQ-16).DiscussionThe proportion of participants scoring ≥6 on the PQ-16 is consistent with the findings from other European studies in the general population and in outpatient mental health settings. The procedures and sample characteristics reported here provide context for further analyses using the ENTER tool. In addition, the findings highlight the considerable challenge of fraudulent and inauthentic responses in online research—an issue that may have been amplified by the use of financial incentives and recruitment via social media.